No caminho da leitura literária ou com a leitura literária em seu caminho - Maria Gorete Paulo Torres; Maria Lúcia Pessoa Sampaio (Universidade do Estado do Rio Grande do Norte, 2013)
This work is the result of a dissertation which identifies that literary texts are read by teachers in the Bachelor's / Portuguese Speaking at a public university. There is still, for what purpose and often the teachers surveyed held a literary reading and how this process occurred. Were used as theoretical studies Antunes (2009), Amarilha (1997 -2006,), Magnani (2001), Machado (2002), Martins (2006), Sampaio (2005), among others, that discuss the process of training of readers and reading for pleasure. This is a qualitative research, and configure as a descriptive and interpretative. Characterized as documentary research, the fact of working with written material firsthand. We use induction as the corpus analysis procedure consisted of statements from teachers already mentioned. The results show that the teachers surveyed held and / or perform readings of a wide variety of literary texts in a constant frequency and that teachers perform literary reading for various purposes, such as for discussion and reflection in the classroom to help understand the theories used in their classes and to feel pleasure.